2014
DOI: 10.1073/pnas.1409869111
|View full text |Cite
|
Sign up to set email alerts
|

The Tn7 transposition regulator TnsC interacts with the transposase subunit TnsB and target selector TnsD

Abstract: The excision of transposon Tn7 from a donor site and its insertion into its preferred target site, attachment site attTn7, is mediated by four Tn7-encoded transposition proteins: TnsA, TnsB, TnsC, and TnsD. Transposition requires the assembly of a nucleoprotein complex containing all four Tns proteins and the DNA substrates, the donor site containing Tn7, and the preferred target site attTn7. TnsA and TnsB together form the heteromeric Tn7 transposase, and TnsD is a target-selecting protein that binds specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Extensive studies on the Mu transposase have revealed that the ATPase subunit MuB associates with the RNase H fold ( 74 ) endoDNase subunit MuA that cuts the target DNA for transposition ( 75 , 76 ). Similar studies on the TN7 transposase have revealed that its ATPase subunit TnsC associates with two subunits, TnsA and TnsB, which contain REase and RNase H fold endoDNase domains, respectively ( 71 , 77 ). In both Mu and TN7 the ATP-bound STAND ATPase is required for association with the target DNA and activates the endoDNase subunits to cut the donor DNA ( 78 , 79 ).…”
Section: Resultsmentioning
confidence: 68%
“…Extensive studies on the Mu transposase have revealed that the ATPase subunit MuB associates with the RNase H fold ( 74 ) endoDNase subunit MuA that cuts the target DNA for transposition ( 75 , 76 ). Similar studies on the TN7 transposase have revealed that its ATPase subunit TnsC associates with two subunits, TnsA and TnsB, which contain REase and RNase H fold endoDNase domains, respectively ( 71 , 77 ). In both Mu and TN7 the ATP-bound STAND ATPase is required for association with the target DNA and activates the endoDNase subunits to cut the donor DNA ( 78 , 79 ).…”
Section: Resultsmentioning
confidence: 68%
“…We thus employed a systematic in vivo photo‐cross‐linking approach to identify possible interacting partners in an unbiased manner (Chin et al ., ; Chin and Schultz, ). This technique has been successfully applied to analysis of protein–protein interactions in a variety of biological processes (Mori and Ito, ; Freinkman et al ., ; Choi et al ., ; Shiota et al ., ; Maklashina et al ., ; Miyazaki et al ., ; Akiyama et al ., ). Each codon for the 179 residues in the entire TPR domain (309–487) was changed to an amber codon by site‐directed mutagenesis to allow suppressor tRNA‐mediated incorporation of a nonnatural, photoreactive amino acid, p ‐benzoylphenylalanine (pBPA).…”
Section: Resultsmentioning
confidence: 97%
“…In multidrug-resistant Enterobacteriaceae bacteria, Tn7-like transposons play a very vital role due to their high capability for transferring antimicrobial resistance genes (37). Through drug susceptibility tests, we found that the multi-drug resistance of Enterobacteriaceae carrying Tn7-like is widespread in various strains.…”
Section: Discussionmentioning
confidence: 92%